One‐Pot Synthesis of Multifunctional Au@Graphene Oxide Nanocolloid Core@Shell Nanoparticles for Raman Bioimaging, Photothermal, and Photodynamic Therapy. Issue 21 (27th January 2015) - Kim, Young‐Kwan; Na, Hee‐Kyung; Kim, Seongchan; Jang, Hongje; Chang, Sung‐Jin; Min, Dal‐Hee
<x xml:space="preserve">Abstract</x> The paper reports a facile one‐pot synthesis of core@shell nanoparticles (NPs) composed of Au core and graphene oxide nanocolloid (GON) shell. Unique properties of Au NPs and GON can be incorporated into a single nanohybrid structure to provide desirable functions for theranosis such as localized surface plasmon resonance, Raman scattering, amphiphilic surface, and photothermal conversion. Synthesis of Au@GON NPs is achieved by simple one‐pot reaction in aqueous phase utilizing GON as a reducing and stabilizing agent without any additional reducing agent. The zinc phthalocyanine, a photosensitizer, loaded Au@GON NPs show excellent multifunctional properties for combinational treatment of photothermal and photodynamic therapy in addition to Raman bioimaging with low cytotoxicity.